Efecto de la sombra la biodiberdidad faunística y calidadad del suelo em ecosistemas cafetaleros del entorno del Cantón Mocache. Periodo 2014-2015. Plan de manejo sostenible, - Guerrero Castillo, Hilton Eduardo (2015)
Mocache area and its surroundings is very common to see logging to devote land to conventional agriculture, which contributes to the disappearance of flora and fauna which generates an environmental impact causing land degradation and microorganisms that exist there. There are lack of information on how to restore or maintain the biodiversity of this area in special in coffee ecosystems in the region, which are handled improperly, leading to the abandonment and low productivity. This research was conducted to evaluate the effect of shade coffee cultivation on the faunal biodiversity and soil quality in coffee ecosystems in the canton Mocache. It is important to understand that the combined crops generate other wildlife species, improve soil conditions and serve as hosts of beneficial insects to the environment, thus achieving a biological balance in the ecosystem. The methodology is based on factors such as the analysis of ecosystems with and without shade and identification of faunal biodiversity in the environment Mocache, also determining the quality of the ecosystem. The results indicate that in agroforestry systems (lot with shade) there is a greater biodiversity of species producing an appropriate habitat for development, also improving the biological activity of the soil and environmental conditions. Finally, the study presents a basic proposal for the sustainable management of faunal biodiversity in coffee ecosystems of Mocache canton